Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jcad.12238
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Coping Mechanisms of Whites Committed to Antiracism

Abstract: Scholars have cited an antiracist identity as an ideal development status for Whites seeking to change systemic racism (Helms, 1995). However, little is known regarding the lived complexities of antiracist work itself. This article examines the experiences of one group of Whites (N = 10) committed to antiracist action. Outcomes indicate challenges that include backlash and struggles to identify more effective antiracist tactics. Coping mechanisms are considered in relation to counseling and counselor training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…The findings reported here are specific to managing personal racism. Additional findings focused on other aspects of autonomy status WRID are reported elsewhere (Malott et al, 2015, 2019).…”
Section: Wridmentioning
confidence: 53%
See 2 more Smart Citations
“…The findings reported here are specific to managing personal racism. Additional findings focused on other aspects of autonomy status WRID are reported elsewhere (Malott et al, 2015, 2019).…”
Section: Wridmentioning
confidence: 53%
“…Scholars have also contested theoretical tenets that describe autonomous Whiteness as nonracist and positive (Linder, 2015; Malott et al, 2015, 2019; Manglitz et al, 2005; O'Brien, 2001; Roediger, 1999). Conversely, Whites have noted positive aspects of their personal racial identity, such as identification with an antiracist identity and lifestyle, which may counterbalance a fundamentally negative definition of White identity (Eichstedt, 2001; Malott et al, 2019). The findings reported here are specific to managing personal racism.…”
Section: Wridmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Kozan and Blustein (2018) reported that practitioners who graduated from a socially just–oriented program gained several advocacy behaviors, such as recognizing impacts of systemic factors on mental health, integrating social justice perspectives into case conceptualization and the therapeutic alliance, adopting nontraditional roles to help clients navigate multiple systems, advocating for culturally responsible practices and policies in their organizations, and addressing power dynamics and contextual issues within the profession. With these benefits, trainees and practitioners noted some difficulty moving from microlevel (i.e., awareness‐building) to macrolevel (i.e., systems collaboration) interventions (Ramirez Stege et al, 2017), which may have resulted from navigating personal needs and social justice goals as well as encountering backlash from peers for their social advocacy efforts (Malott, Schaefle, Paone, Cates, & Haizlip, 2019).…”
Section: Scholarship: a Brief Reviewmentioning
confidence: 99%
“…Limitations of previous scholarship include (a) how social justice counseling and social justice counseling competencies are operationalized by practitioners and clients (Ramirez Stege et al, 2017; Schriberg & Clinton, 2016); (b) how social justice competency develops as an aspect of multicultural competency (Crook et al, 2015; Hays, 2008; Presseau et al, 2018); (c) what social justice counseling efforts are enacted by counselors (Malott et al, 2019); and (d) at what levels of intervention, and to what degree, counselors and clients experience social injustice or barriers to social justice work and the impact of those experiences on counseling process and outcome (Crook et al, 2015; Kozan & Blustein, 2018). Hays and Dahl (in press) suggested indicators of MSJCC research effectiveness at the six intervention levels (see Ratts et al, 2016).…”
Section: Research Gaps and Future Directionsmentioning
confidence: 99%